The Bastion of Liberty Leiden University Today and Yesterday - Otterspeer, Willem (LUP Academic, 2008)
Leiden University was conceived as the embodiment of specifically academic ethics which sought to improve society through a cumulative process of knowledge acquisition. Drawing on the idea of Leiden as a 'bastion of liberty', the renowned historian Willem Otterspeer proposes that concepts such as 'equilibrium' and 'mediation' are key to understanding the university as an institution. Modernity and scale expansion have made Leiden University a different institution in the twentyfirst century, one scarcely comparable to what had gone before. As this lively and erudite study shows, a university is a form of social capital, one of Western society's answers to the dilemma of collective action, an instrument for preserving and restoring equilibrium, and hence for fostering continuity. From this vantage point, a university is a confidence-building mechanism that generates solutions to the serious problems facing society today. Also available in Dutch: "http://www.aup.nl/do.php?a=show_visitor_book&isbn=9789087280246">ISBN 978 90 8728 024 6